Proceedings of the 2007 Conference on Designing Pleasurable Products and Interfaces 2007
DOI: 10.1145/1314161.1314180
|View full text |Cite
|
Sign up to set email alerts
|

How interface agents affect interaction between humans and computers

Abstract: For many years, the HCI community has harbored a vision of interacting with intelligent, embodied computer agents. However, the reality of this vision remains elusive. From an interaction design perspective, little is known about how to specifically design an embodied agent to support the task it will perform and the social interactions that will result. This paper presents design research that explores the relationship between the visual features of embodied agents and the tasks they perform, and the social a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
3
3

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(45 citation statements)
references
References 14 publications
0
35
0
Order By: Relevance
“…Similarly, Forlizzi et al (2007) find effects for agent appearance that reflect common gender stereotypes.…”
Section: Robot Appearancementioning
confidence: 90%
“…Similarly, Forlizzi et al (2007) find effects for agent appearance that reflect common gender stereotypes.…”
Section: Robot Appearancementioning
confidence: 90%
“…Previous research has demonstrated that humans treat computers as if they were social actors, even though they do not exhibit anthropomorphic traits [5]. By adding a face and embodiment to an interface the social relationship between user and computer becomes even more explicit: clothing, facial expression, hairstyle, gender and age cues displayed by an agent bring the rich and complex world of human social interactions into the interface [6].…”
Section: Related Workmentioning
confidence: 99%
“…The anthropomorphic design should be emphasized with the elements of presence and responses. Previous works related to the elements of presence on the anthropomorphic interfaces include the element of gender, ethnicity, facial attractiveness (Angeli & Khan, 2007;Forlizzi, Zimmerman, Mancuso, & Kwak, 2007;Qiu & Benbasat, 2010), and age (Yoo, Peña, & Drumwright, 2015). Meanwhile, previous works such as Cowell & Stanney (2005) Gong (2008) and Złotowski, Strasser, & Bartneck (2014) considered the eye contact, facial expression, posture, voice, emotion, and intelligence as the element of responses.…”
Section: Anthropomorphic Interfaces Gamificationmentioning
confidence: 99%